Both HDAC5 and HDAC6 are required for the proliferation and metastasis of melanoma cells. Issue 1 (December 2016) - Liu, Jiaqi; Gu, Jianying; Feng, Zihao; Yang, Yanhong; Zhu, Ningwen; Lu, Weiyue; Qi, Fazhi
Abstract Background Histone deacetylase (HDAC) inhibitors are widely used in clinical investigation as novel drug targets. For example, panobinostat and vorinostat have been used to treat patients with melanoma. However, HDAC inhibitors are small-molecule compounds without a specific target, and their mechanism of action is unclear. Therefore, it is necessary to investigate which HDACs are required for the proliferation and metastasis of melanoma cells. Methods We used overexpression and knocking down lentivirus to clarify the influence of HDAC5 and HDAC6 in melanoma development. Also, we introduced stable HDAC5 or HDAC6 knockdown cells into null mice and found that the knockdown cells were unable to form solid tumors. Finally, we tested HDAC5 and HDAC6 expression and sub-location in clinical melanoma tissues and tumor adjacent tissues. Results In this study, and found that HDAC5 and HDAC6 were highly expressed in melanoma cells but exhibited low expression levels in normal skin cells. Furthermore, we knocked down HDAC5 or HDAC6 in A375 cells and demonstrated that both HDAC5 and HDAC6 contributed to the proliferation and metastasis of melanoma cells. Conclusions This study demonstrated both HDAC5 and HDAC6 were required for melanoma cell proliferation and metastasis through different signaling pathways.